ANALYSIS OF THE DIFFICULTIES OF CLASS VII MIDDLE SCHOOL STUDENTS IN SOLVING ALGEBRA OPERATIONS PROBLEMS BASED ON GENDER - Melia Ulfa (Prodi Tadris Matematika Universitas Muhammadiyah Aceh, 2023)
In the process of learning mathematics, there are children who enjoy mathematics if they understand the basics of the material being taught. Meanwhile, children who do not master the basic concepts of the material tend to view mathematics as something unpleasant, one of which is algebraic operations material. In the process of teaching and learning activities, students experience difficulties in understanding variables, coefficients and constants, and are confused about differentiating between similar and dissimilar terms. This study aims to determine the difficulties experienced by class VII junior high school students in solving algebraic operations questions based on gender. This research uses qualitative methods with a descriptive type and tends to use analysis. In this study, the research subjects were class VII students at MTsS Baitul Arqam Aceh Besar, consisting of 6 students, including 3 male students and 3 female students. Data was collected through tests and interviews and then the data was analyzed through data reduction, presenting data and drawing conclusions. The research results showed that: (1) female subjects with high difficulty (NNPT) and male subjects with high difficulty (ZALT) experienced difficulties with indicators of concepts and principles, namely: difficulty expressing concepts, difficulty grouping similar and unlike terms and difficulty in completing simplifications. subtracting algebraic fractions. (2) female subjects with moderate difficulty (NTPS) and male subjects with moderate difficulty (FGLS) experienced difficulties with concept indicators, namely: difficulty restating concepts, students only memorized definitions. In determining like and unlike terms the subject did not experience any difficulties, but the subject did not read the question carefully so the answer was wrong. (3) female subjects with low difficulty (KPPR) and male subjects with low difficulty (SYLR) only experienced difficulties with the principle indicators, namely: difficulty in simplifying algebraic forms. Keywords: Analysis of Student Difficulties, Algebra Operations, Gender.